First results on the genetic diversity of the invasive signal crayfish Pacifastacus leniusculus (Dana, 1852) in Europe using novel microsatellite loci - Froufe, Elsa (2015)
The introduction of non-native crayfish in aquatic ecosystems is very common due to human activities (e.g. aquaculture, recreational and commercial fisheries). The signal crayfish, Pacifastacus leniusculus (Dana, 1852), is one of the most widespread invasive species in Europe. Although several important ecological and economic impacts of this species have been reported, its European population genetic characterisation has never been undertaken using nuclear markers. Thus, the aim of this study was to develop and characterise new microsatellite markers for signal crayfish that can be useful in future studies in its invaded range, since only five are available so far. In total, 93 individuals from four geographically distinct European populations (Portugal, Great Britain, Finland and Sweden) were scored for the new markers and for those previously described, with the Bayesian analysis revealing a clear distinction among populations. These markers are suitable for future studies of the population genetic structure of this important invasive species, by increasing information about the possible pathways of introduction and dispersal, and by giving insights about the most important vectors of introduction.